PENDEKATAN PEMBELAJARAN BERBASIS PROYEK DI SEKOLAH DASAR (INDIKASI TERHADAP KREATIVITAS DAN KEMANDIRIAN SISWA) - Ayuni, Ayuni (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2026)
Project-Based Learning (PjBL) is an innovative learning approach that is student- centered and emphasizes meaningful learning experiences through project activities. This research aims to examine the implementation of PjBL in elementary schools and its indications of increasing student creativity and independence. The method used is a literature review by analyzing various relevant literature sources, such as books, scientific journals and official educational documents. The results of the study show that PjBL makes a positive contribution to the development of student creativity, which is characterized by the ability to generate diverse ideas, think flexibly, and create original solutions. Apart from that, PjBL also has implications for increasing student learning independence, which can be seen from the ability to plan, manage and evaluate the learning process independently. The implementation of PjBL in elementary schools also encourages changes in the role of teachers to become facilitators and the use of authentic assessment in learning. Thus, PjBL can be an effective alternative learning approach in improving the quality of basic education, especially in developing students' creativity and independence in accordance with the demands of 21st century education.